This could be us - Ryan, Kennedy (The Skyland series, 2024)
"Soledad Barnes has her life all planned out. Because, of course, she does. She plans everything. She designs everything. She fixes everything. She's a domestic goddess who's never met a party she couldn't host or a charge she couldn't lead. The one with all the answers and the perfect vinaigrette for that summer salad. But none of her varied talents can save her when catastrophe strikes, and the life she built with the man who was supposed to be her forever, goes poof in a cloud of betrayal and disillusion. But there is no time to pout or sulk, or even grieve the life she lost. She's too busy keeping a roof over her daughters' heads and food on the table. And in the process of saving them all, Soledad rediscovers herself. From the ashes of a life burned to the ground, something bold and new can rise. But then an unlikely man enters the picture--the forbidden one, the one she shouldn't want but can't seem to resist. She's lost it all before and refuses to repeat her mistakes. Can she trust him? Can she trust herself? After all she's lost . . .and found . . .can she be brave enough to make room for what could be?"--